OsMas1, a novel maspardin protein gene, confers tolerance to salt and drought stresses by regulating ABA signaling in rice - Fei-bing WANG; Chen-zhong WAN; Hao-fei NIU; Ming-yang QI; Gang LI; Fan ZHANG; Lai-bao HU; Yu-xiu YE; Zun-xin WANG; Bao-lei PEI; Xin-hong CHEN; Cai-yong YUAN (Journal of Integrative Agriculture, 2023)
Drought and salt stresses, the major environmental abiotic stresses in agriculture worldwide, affect plant growth, crop productivity, and quality. Therefore, developing crops with higher drought and salt tolerance is highly desirable. This study reported the isolation, biological function, and molecular characterization of a novel maspardin gene, OsMas1, from rice. The OsMas1 protein was localized to the cytoplasm. The expression levels of OsMas1 were up-regulated under mannitol, PEG6000, NaCl, and abscisic acid (ABA) treatments in rice. The OsMas1 gene was introduced into the rice cultivar Zhonghua 11 (wild type, WT). OsMas1-overexpression (OsMas1-OE) plants exhibited significantly enhanced salt and drought tolerance; in contrast, OsMas1-interference (OsMas1-RNAi) plants exhibited decreased tolerance to salt and drought stresses, compared with WT. OsMas1-OE plants exhibited enhanced hypersensitivity, while OsMas1-RNAi plants showed less sensitivity to exogenous ABA treatment at both germination and post-germination stages. ABA, proline and K+ contents and superoxide dismutase (SOD), catalase (CAT), peroxidase (POD), and photosynthesis activities were significantly increased. In contrast, malonaldehyde (MDA), hydrogen peroxide (H2O2), superoxide anion radical (O2-·), and Na+ contents were significantly decreased in OsMas1-OE plants compared with OsMas1-RNAi and WT plants. Overexpression of OsMas1 up-regulated the genes involved in ABA signaling, proline biosynthesis, reactive oxygen species (ROS)-scavenging system, photosynthesis, and ion transport under salt and drought stresses. Our results indicate that the OsMas1 gene improves salt and drought tolerance in rice, which may serve as a candidate gene for enhancing crop resistance to abiotic stresses.